1997
DOI: 10.1152/jn.1997.77.4.1924
|View full text |Cite
|
Sign up to set email alerts
|

Differential Epilepsy-Associated Alterations in Postsynaptic GABAA Receptor Function in Dentate Granule and CA1 Neurons

Abstract: Alterations in GABAergic function associated with the development of temporal lobe epilepsy (TLE) were examined with the use of patch-clamp recording techniques in dentate granule (DG) and CA1 neurons acutely isolated from control and spontaneously epileptic rats in which TLE was elicited by pilocarpine injection 3-17 wk before use. The maximal efficacy of gamma-aminobutyric acid (GABA) in activating whole cell GABA currents increased significantly in epileptic DG neurons relative to controls. This efficacy in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
155
3
3

Year Published

1999
1999
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(174 citation statements)
references
References 40 publications
(10 reference statements)
13
155
3
3
Order By: Relevance
“…At 2 weeks after virus injections, a subset of rats was exposed to PILO-induced SE according to a standard protocol (6,24). PILO injection triggered long-duration (Ͼ30 min) seizures within 10-30 min after injection.…”
Section: Induction Of Status Epilepticus (Se)mentioning
confidence: 99%
“…At 2 weeks after virus injections, a subset of rats was exposed to PILO-induced SE according to a standard protocol (6,24). PILO injection triggered long-duration (Ͼ30 min) seizures within 10-30 min after injection.…”
Section: Induction Of Status Epilepticus (Se)mentioning
confidence: 99%
“…All experiments were performed in accordance with the National Institutes of Health Guidelines for the Care and Use of Laboratory Animals and with the approval of the Children's Hospital of Philadelphia Institutional Animal Care and Use Committee. Pilocarpine animals were produced using previously reported methods (Gibbs et al, 1997). Adult male Sprague Dawley rats (180 -200 g) were pretreated with scopolamine methyl nitrate (1 mg/kg, s.c.) to antagonize peripheral effects induced by subsequent pilocarpine (405 mg/kg, s.c.), injected 30 min later.…”
Section: Methodsmentioning
confidence: 99%
“…Breakdown of the dentate "gate" has been hypothesized to be a primary contributor to seizure generation in epilepsy (Sutula et al, 1988;Heinemann et al, 1992;Lothman et al, 1992;Mello et al, 1993). Paradoxically, several TLE studies have indicated that inhibition within the dentate remains operative, and suppresses seizure propagation from the entorhinal cortex (Gibbs et al, 1997;Wilson et al, 1998;Wu and Leong 2001;Sloviter et al, 2006). Despite the controversy concerning the state of gate function of the dentate gyrus and disrupted intrinsic circuitry, the hippocampus remains critical in seizure generation.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas some forms of epilepsy have been associated with mutations in genes coding for ion channels and ␥-aminobutyric acid (GABA) receptors (1,2); there is no clear genetic background in the refractory TLE patients. Nevertheless, there are clear associations to changes in metabolite concentrations (3), modifications in the properties of receptor and transporter systems of excitatory and inhibitory amino acid neurotransmitters (4 -6), changes in signaling proteins of postsynaptic densities (7), altered expression of neurotransmitter receptors (6,8,9), and altered GABA activity (10,11). Thus, epileptogenesis, extensively investigated in both animal models and humans, may be related to many events, including GABA type A receptor (GABA A -receptor) dysfunction (12).…”
mentioning
confidence: 99%